2019
DOI: 10.1177/1528083719842793
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermoregulation properties of various ceramic-containing knitted fabric structures

Abstract: To ensure the thermal comfort during high physical activity, clothes must have good thermoregulation properties. Textiles containing ceramic additives, which are able to absorb and emit back the thermal energy from the human body, can be used to improve the thermal properties of the fabric. The aim of the research was to investigate the thermal and moisture management properties of different, three-layer knitted fabrics containing fibers impregnated with infrared-emitting ceramic particles. The thermal efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…The moderation of heat build-up is known to be directly related to the amount of bioceramic additives, being more effective the greater the percentage [37]. In this study, we opted to investigate the potential decrease in the post-running temperatures of the feet of the athletes wearing a sock with just a single bioceramic content (1%).…”
Section: Application and Limitations Of The Studymentioning
confidence: 99%
“…The moderation of heat build-up is known to be directly related to the amount of bioceramic additives, being more effective the greater the percentage [37]. In this study, we opted to investigate the potential decrease in the post-running temperatures of the feet of the athletes wearing a sock with just a single bioceramic content (1%).…”
Section: Application and Limitations Of The Studymentioning
confidence: 99%
“…Incorporated micro-and nano-particle-sized far-infrared (FIR) accumulating minerals (magnesium, zirconium and iron oxides, silicon carbide and germanium compounds, etc.) exhibit the ability of the human body to accumulate/release heat [65][66][67][68][69]. The most important part of creating a human sense of heat is the far-infrared spectrum of IR radiation, namely electromagnetic waves of 6-15 mm long, because only waves of that length of FIR radiation emitted by heat can be received and delivered to the human body [67,70].…”
Section: Resultsmentioning
confidence: 99%
“…The most important part of creating a human sense of heat is the far-infrared spectrum of IR radiation, namely electromagnetic waves of 6-15 mm long, because only waves of that length of FIR radiation emitted by heat can be received and delivered to the human body [67,70]. Therefore, this innovative fibre has not only protective functions but also provides an enhanced thermoregulatory effect: it balances temperature fluctuations and provides an enhanced thermal effect [69,71]. The PCM efficiency (DH) of the yarns consisting Cell Solution V R Protection fibre fibers, determined by DSC analysis: absorbed heat at 3.441 J/g and released heat at 3.242 J/g (see Figure 9(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Pooley et al 12 reported calculated emissivity in FIR region of TiO 2 imbedded fabrics and compared it with the emissivity measured using TSS-5X measuring equipment. Stygiene et al 13 examined the thermoregulation of various ceramic included knitted fabrics made of bioceramic polyethylene terephthalate (PET) spun yarns (Resistex ® and Mirawave ® ) and PA66 textured microfiber filament (Nilit ® ). They measured moisture vapor permeability, water absorbing and drying properties, heat release temperature by infrared (IR) rays with the elemental analysis by Bruker X-ray and morphological investigation by scanning electron microscope (SEM) analysis.…”
Section: Introductionmentioning
confidence: 99%